Digital Leadership in Education: Leveraging Technology for Effective Learning in Pesantren - Irwan Budi Efendi; Busthomi Ibrohim (International Journal of Learning and Education, 2026)
The rapid advancement of digital technology has fundamentally reshaped the educational landscape, compelling institutions, including pesantren, to adopt technology-enhanced pedagogical approaches. This study aims to examine the role of digital leadership in optimizing the effectiveness of technology-based learning within pesantren and to develop a comprehensive framework that integrates digital leadership dimensions with instructional innovation in the Indonesian Islamic educational context. Employing a systematic literature review methodology, this study analyzed 52 peer-reviewed articles published between 2020 and 2025, retrieved from Scopus, Web of Science, and ERIC databases. The selection process followed the PRISMA 2020 guidelines, incorporating keyword-based searches, inclusion and exclusion criteria, and thematic content analysis to synthesize findings across multiple disciplinary perspectives. The findings reveal that digital leadership, encompassing five core dimensions of visionary leadership, digital-age learning culture, excellence in professional practice, systemic improvement, and digital citizenship, exerts a significant positive influence on teacher performance and, indirectly, on the development of students’ twenty-first-century competencies. The study further identifies that professional learning communities serve as a critical mediating variable between digital leadership and sustainable technology integration. The novelty of this study lies in its integrative synthesis of the digital leadership-learning effectiveness nexus within the specific context of Indonesian pesantren, highlighting the indirect pathway through which digital leadership enhances student outcomes via teacher empowerment and digital facilitation roles.